2003
DOI: 10.4141/s03-001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eight years of crop rotation and tillage on nitrogen availability and budget of a sandy loam soil

Abstract: Soon, Y. K. and Clayton, G. W. 2003. Effects of eight years of crop rotation and tillage on nitrogen availablity and budget of a sandy loam soil. Can. J. Soil. Sci. 83: 475-481. The effects of tillage and crop rotations on soil N availability and economy were evaluated over two rotation cycles to address the paucity of such information. From 1993 through 2000, soil was sampled to 120 cm in the autumn from four crop rotations : (i) continuous wheat (Triticum aestivum L.), (ii) field pea (Pisum sativum L.)-wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Although soil under CT had on average 12 kg ha -1 more NO 3 -N in the 15-to 60-cm depth at sowing than soil under NT (P = 0.02), this had no effect on crop N uptake, utilization and yield, suggesting that NO 3 -in subsoil may not be efficiently exploited by crops. Soil NO 3 content is typically higher under CT compared with NT (Nyborg and Malhi 1989;Grant and Lafond 1994;Soon and Clayton 2003). However, growing season N min was not significantly affected by tillage.…”
Section: General Discussion and Conclusionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although soil under CT had on average 12 kg ha -1 more NO 3 -N in the 15-to 60-cm depth at sowing than soil under NT (P = 0.02), this had no effect on crop N uptake, utilization and yield, suggesting that NO 3 -in subsoil may not be efficiently exploited by crops. Soil NO 3 content is typically higher under CT compared with NT (Nyborg and Malhi 1989;Grant and Lafond 1994;Soon and Clayton 2003). However, growing season N min was not significantly affected by tillage.…”
Section: General Discussion and Conclusionmentioning
confidence: 88%
“…Conversely, NT tends to conserve soil organic matter. Consequently, soil NO 3 has more frequently than not been reported to be higher in the fall or spring under CT than under NT or minimum tillage (MT) (Nyborg and Malhi 1989;Grant and Lafond 1994;Soon and Clayton 2003). In the prairies, cereal yields and/or N uptake tend to be higher under CT than NT when (i) available water is adequate, but the opposite trend prevails when available water is low (Halvorson et al 2000); and (ii) N supply is low, whereas yields are similar when N supply is adequate (Nyborg and Malhi 1989;Malhi and Nyborg 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower extractable inorganic N concentrations are attributed to greater N immobilization when straw was retained, especially when incorporated into the soil by tillage. We have previously shown that in the fall, total NO 3 -content in the rooting zone tended to be higher under CT than NT (Soon and Clayton 2003;Soon and Arshad 2004). Soil NO 3 -content has been reported to be greater in the subsurface layers under CT than NT (Grant and Lafond 1994) or unaffected by tillage practices (Malhi et al 1992).…”
Section: Resultsmentioning
confidence: 94%
“…These studies only determined N balance for the year of pulse crop cultivation rather than the entire cropping sequence. Soon & Clayton (2003) showed that N exported in grains over a 4-year rotation cycle was only 3-7 kg/ha more than N input through N 2 fixation and recommended rates of fertilizer application for a pea-wheat-canola-wheat rotation. The N removal was similar to a continuous wheat rotation, however, 0 .…”
Section: Introductionmentioning
confidence: 99%